Trade Issues in East Asia : Preferential Rules of Origin - World Bank (Washington, DC, 2014)
Rules of origin are a necessary feature of any regional trade agreement. They ensure that preferences are available only to the signatories of the agreement and that imports from non-members do not avoid customs duties by entering through the member with the lowest tariff. The rules of origin define the amount of local processing, or the extent of the transformation of the product, that must be undertaken in the country from which the product claiming preferences is exported. The definition of these requirements to prevent trade deflection is not straightforward. If the rules are too onerous and complex and are costly to comply with, they will limit the impact of tariff reductions on trade. Indeed, import competing industries have often been successful in obtaining restrictive rules of origin that dilute the impact of the loss of tariff protection. This is most apparent in agreements between developed countries and lower wage countries. As FTAs multiply in the region, putting in place rules of origin (ROO) that are simple, transparent, and easy to implement becomes important. The experience in the implementation of the AFTA rules of origin can provide some lessons for the upcoming FTAs.